A compositional analysis of VP anaphors - Gabriel Flambard (Anglophonia)
The VP anaphors do it and do this/do that have been little studied in the literature, although they are mentioned in passing in a number of more general works such as Hankamer and Sag (1976), Culicover and Jackendoff (2005) or descriptive grammars by Quirk et al. (1985) or Huddleston and Pullum (2002). With the exception of Souesme (1985), very few extant studies are available and there are almost none that explore the internal structure of VPAs in detail. This paper argues for a compositional analysis of the structure of VPAs, proposing that they are ordinary transitive constructions of the form ‘do + object pronoun’ and, following Simner (2001) and Stroik (2001), that it is the pronoun, rather than the VP expression as a whole, which serves as the anaphoric element. The compositional nature of VPAs is evidenced by a range of syntactic and semantic facts which point to the relative independence of main verb do and the object pronoun in such constructions. Foremost among these is the very possibility of alternating between it and demonstrative pronouns, which is itself highly suggestive of a compositional structure. Further evidence is supplied by passivisation (it/this/that was done) or pseudo-clefting with do this/that (This/That is what I did). Secondly, we will address the question of how both parts of the VP contribute to its interpretation. Object pronouns in VPAs are distinguished by having a VP as their antecedent, or ‘antecedent-trigger’, as Cornish (1992, 1996) calls the segment of discourse through which an appropriate antecedent is retrieved. The anaphoric relation between the object pronoun and the VP trigger holds regardless of the fact that the pronoun cannot be replaced with any VP expression (e.g. * John did {mowing/ (to) mow} the lawn), as replaceability is not a necessary condition for antecedenthood.